AKUNTABILITAS PEJABAT PENGAWAS LINGKUNGAN HIDUP DI BADAN LINGKUNGAN HIDUP (BLH) KABUPATEN SIGI - Murniati, Murniati (Katalogis, 2016)
This study aims to identify and analyze the accountability of officials of the environment watchdog use descriptive research qualitative approach, to measure accountability based on the opinions Sedarmayanti (2004: 12), which states that the accountability is: control environment in accordance with transparent, monitoring environmental efficient and effective and responsive environmental monitoring. The collection of data through observation, interview, and documentation, dianlisis through the stages of data reduction, data display, and conclusion. The study concluded that, officials of the Environment (PPLH) at the Environment Agency Sigi not accountable in carrying out its duties. It can be seen from liability in accordance with provisions of environmental monitoring and transparency, has not been implemented properly in addition to not have a standard operating procedure (SOP), the supervision of compliance with the environment, not in accordance with the provisions and less transparan.Pertanggungjawaban on environmental monitoring has not menerepkan principle the efficiency and effectiveness of the well based on the provisions in force and use the standard operating procedures (SOP). The task of inspecting the observance, collecting documents and testify against the evidence that was found had not been effective, because the environment watchdog officials have not been able to maintain the accuracy and quality assurance monitoring results during an inspection or investigation of business and / or activity. Similarly, supervisory accountability environment that is responsive, generally the environmental watchdog officials have not responded well to the aspirations of society as a feedback to maximize the task. Not to akuntabelnya environmental watchdog official duty stints environmental surveillance, due to limited funds/operating budget travel to conduct regular supervision and inspection.